Factorise : 6x^2 + 5 − 6
Answers
Answered by
3
Answer:
hope its helpful
Step-by-step explanation:
We can Split the Middle Term of this expression to factorise it.
In this technique, if we have to factorise an expression like a x 2 + b x + c , we need to think of 2 numbers such that: N 1 ⋅ N 2 = a ⋅ c = 6 ⋅ ( − 6 ) = −36
and, N1 + N 2 = b = − 5
After trying out a few numbers we get N 1 = − 9 and N 2 = 4
( − 9 ) ⋅ 4 = − 36 , and − 9 + 4 = − 5
6 x 2 − 5 x − 6 = 6 x 2 − 9 x + 4 x − 6
= 3 x ( 2 x − 3 ) + 2 ( 2 x − 3 )
( 2 x − 3 ) is common to both the terms
( 3 x + 2 ) ( 2 x − 3 ) is the factorised form
Similar questions
Math,
5 months ago
Business Studies,
5 months ago
Computer Science,
10 months ago
Biology,
10 months ago